2014
DOI: 10.17219/acem/37140
|View full text |Cite
|
Sign up to set email alerts
|

Is Additional Enrichment of Diet in Branched-Chain Amino Acids or Glutamine Beneficial for Patients Receiving Total Parenteral Nutrition after Gastrointestinal Cancer Surgery?

Abstract: Objectives. Total Parenteral Nutrition (TPN) is necessary in patients unable to receive oral or enteral feeding for a period of at least 7 days. branched-chain amino acids (bcaa): valine (Val), leucine (Leu), and isoleucine (Ile) are essential amino acids, which are important regulators in protein metabolism. They are also the main nitrogen source for glutamine synthesis in muscles. In this process they undergo irreversible degradation and cannot be reutilised for protein synthesis. In catabolic states, like c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(36 reference statements)
2
5
0
Order By: Relevance
“…We found that isoleucine is decreased in CSF in rats after cerebral ischemic reperfusion injury, which is consistent with the recent metabolomics profiling on plasma of the acute stroke patients (39)(40)(41)(42). Unexpectedly, we further show that intraneuronal isoleucine is increased after OGD insult.…”
Section: Discussionsupporting
confidence: 91%
“…We found that isoleucine is decreased in CSF in rats after cerebral ischemic reperfusion injury, which is consistent with the recent metabolomics profiling on plasma of the acute stroke patients (39)(40)(41)(42). Unexpectedly, we further show that intraneuronal isoleucine is increased after OGD insult.…”
Section: Discussionsupporting
confidence: 91%
“…The result indicated that BCAA could not promote cell transformation, even at very high concentration (16 times higher than serum concentration, Fig. S1b) (Areces et al, 2015, Kooman et al, 1997, Szpetnar et al, 2014). Next, we detected the concentration of BCAA in the serums from 31 normal people and CRC patients or in the tissues from 10 CRC patients paired tumor and corresponding tumor adjacent tissues.…”
Section: Resultsmentioning
confidence: 96%
“…In fact, operation day appeared to have a greater impact on plasma amino acid levels. A recent study that investigated the changes in plasma BCAA and glutamine concentrations in operative gastrointestinal cancer patients indicated that the fall in BCAA levels were partially prevented by total parenteral nutrition [ 43 ]. Our results did not exhibit such an effect on BCAA, whereas AAA appeared to remain at higher levels during the treatment.…”
Section: Discussionmentioning
confidence: 99%